CLASH BETWEEN TWO RESIDENTS IN PROBOLINGGO DUE TO THE ACTUAL LAND RIGHT HOLDER DISPUTE - Amajida Firdauz Putri; Mohamad Fajri Mekka Putra (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
This study aims to evaluate the reliability of land title evidence, including tax stakes and land certificates, both of which are issued by authorized institutions in good faith to individuals, corporations, or other legal entities. The most typical way to acquire land rights is through transferring rights, though there are other ways. However, disagreements over the actual owners of the rights develop as a result of changing times and laws. Since two owners acknowledge that one of them is the valid owner of the land, there is a disagreement between 2 (two) residents in this writing. While the other party has a certificate obtained through the buying and selling process, one of the parties has evidence in the form of an Excerpt Letter C Book. Both are accepted as valid proof for land ownership. However, more investigation is required to determine how strong each proof is and how land rights are acquired and transferred.